Adequação da metodologia dáder em pacientes hospitalizados comm pé diabético : abordagem em atenção farmacêutica - Reis, Henry Pablo Lopes Campos e (2005)
The podologic complications liked to Diabetes mellitus (DM) constitute a serious problem faced by the health system. Its treatment has a high social and economic cost. The pharmacist can contribute to the improvement of the quality of the proposed pharmacotherapy through the use of methodologies for the implementation and divulgation of Pharmnaceutical Care in hospital settings as well. The present study aims to carry out the Drug Therapy Follow-up, of inpatients with diabetc foot, at Dr. Waldemar de Alcântara General Hospital, through Dáder Pharmaceutical Care Methodology, by observing descriptive aspects of the adjustment and feasibility. Thus, a Drug Therapy Follow-up of 53 patients was carried out from November 2003 to March 2004, according to the steps suggested in the methodology (service offer, first interview, diagnostic, study phase, evaluation phase, intervention outcomes phase, new diagnostic, with appropriate adjustments to local needs. Drug-Related Problems (DRP) were classified according to the second Consensus of Granada(2002). Data set up analysis were executed using computer programs, mainly Access and SPSS. The methodological adjustments involved the structure of the Drug Therapy Follow-up record card, of the HENPA Method of codification of the non-conformities of the pharmacotherapy cicle, of the scales for the measurement of the disease perception of the caregiver and the patient, and also of the domiciliary pharmacotherapy used and the necessary forms for communications and outcomes record, and the instruments used for the follow-up. Most patients were from Fortaleza, with average age of 66 yaers, and low schooling. Hospitalization average time was 19 days. When amputation was necessary for more than half of the diabetes follwed-up. The evaluation of the degree of perception of caregiver the patients with relation to DM and its correlations showed they have little knowledge of the various aspects. A statiscally significant relation was observed (p<0,05) between the level of knowledge of the DM complications and treatment. 57,2 DRP/patien (atotal of 3030 DRP), of whom 75% were potencial. The most displayed DRP class was regular insulin. The most suggested pharmaceutical interventions were related to drug administration and prescrition, respectively, base don internal written communication. The adoption of Pharmaceutical Care, through the application of Dáder methodology contextualized an important strategy for the rational use of drugs and the revival of pharmacist’s social role.